Teacher as Mediator: How Teacher Interacts with Parents of the Victim and Agent in School Conflict - Yu, Guodong; Wang, Chaoqiang (Contrastive Pragmatics, 2023)
Abstract The focus of this article is to compare and contrast how teachers interact with parents about their children's involvement in school conflicts. To showcase tricky social interactions of this kind, we choose conversation analysis as a contrastive analysis method and take a pair of telephone calls in which a teacher calls the respective parents of the agent and victim involved in a school fight. Data analyses show that the teacher minimizes incident severity and reasonably attributes responsibility in her call to the victim's parent to prompt forgiveness, whereas attributes full responsibility and maximizes incident severity in her talk with the agent's parent to press for apology. In their responses, both parents build up "good child" and "good parent" identities and seek for the teacher's affiliation with their parenting. The mediation calls end when mutual alignment and affiliation are achieved.